A theology of love : the dynamic of Wesleyanism - Wynkoop, Mildred Bangs (Kansas City, MO : Beacon Hill Press of Kansas City, 2015)
"In this seminal work on holiness Mildred Wynkoop brought to the forefront the understanding that holiness is relational. Here she explains that loving God and loving neighbor find articulate expression in the holy life--a life oriented in dynamic and loving relationship toward God that in turn reaches out and embraces others." -- Back cover
The Wynkoop revolution / Thomas A. Noble -- Wynkoop and the credibility gap / H. Ray Dunning -- Preface -- Concerning references to Wesley's writings -- The clue -- Toward a theology of love -- The credibility gap -- What is Wesleyanism? -- A hermeneutical approach to Wesley -- Man, made in the image of God -- New Testament man -- Sin and holiness -- The meaning of moral -- The psychology of holiness -- The divine-human interaction -- The function of faith -- The clean heart -- Christian perfection -- Sanctification: the substance -- Sanctification: the circumstance -- The lost chapter / David B. McEwan -- Wynkoop and the preaching of holiness / T. Scott Daniels -- A note from archives / Stan Ingersol -- The preaching of holiness -- Someone rather important / Diane Leclerc -- Wynkoop and the Fundamentalist challenge / Stan Ingersol.
Includes bibliographical references (pages 395-403) and indexes.
This new edition includes the original text, a previously unpublished chapter (The preaching of holiness) and additional commentary by Thomas A. Noble, T. Scott Daniels, H. Ray Dunning, Diane Lecler, and David B. McEwan.
Print version record.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Wesley, John, -- 1703-1791.; Church of the Nazarene -- Doctrines; Wesley, John, -- 1703-1791.; Church of the Nazarene; Holiness; Sanctification; Holiness; Sanctification; Theology, Doctrinal; Wesley, John, -- 1703-1791.; RELIGION / Christianity / Methodist; Electronic books; Electronic books